Design of mono-symmetric I-sections under combined load cases by the Overall Interaction Concept. (January 2023) - Li, Liya; Boissonnade, Nicolas
Abstract: This paper reports on in-depth finite element analyses relative to the local buckling behaviour and ultimate resistance of mono-symmetric I-sections under combined load cases. Non-linear numerical models are first developed and validated against existing test results and then used to carry out extensive parametric studies considering wide ranges of steel grades, section slenderness, mono-symmetric degrees and loading situations. The numerical results are used as references to analyse the structural performance of hot-rolled and welded mono-symmetric I-sections under combined load cases, and to assess the accuracy of design equations based on the Overall Interaction Concept (O.I.C.) approach. The O.I.C.-based proposal is shown to yield accurate, consistent and continuous resistance predictions; conversely, both Eurocode 3 and AISC 360 reveal over-conservative predictions. Finally, a statistical analysis following the guidelines of EN 1990 is performed, quantifying the reliability level of the proposed O.I.C. approach. Highlights: The local buckling behaviour of mono-symmetric I-sections was numerically investigated. The O.I.C. design for mono-symmetric I -sections under combined loading cases was proposed. The O.I.C. proposals provide more accurate resistance predictions than current codes.